FINANCIAL SUPPORT TO FRUIT AND VEGETABLES GROWING AND IMPACT ON B&H TRADE BALANCE - Ćosović, Vanja; Vlašković, Vesela; Stakić, Budimir (Economics of Agriculture, 2019)
Data on global competitiveness and trade balance fall within the most important indicators regarding the shape of economy in a specific country. Data for Bosnia and Herzegovina (B&H), are not very good according to either of the said indicators. In regard to competitiveness, the World Economic Forum (WEF) classifies B&H below the average, while the trade balance shows deficit for the past few years in a row. The goal of this paper is, in such situation, to point to one of the bright points, the agricultural sector, primarily fruit and vegetable growing, which, with financial assistance, in a relatively short time period could significantly change B&Hs trade balance. Since the largest volume of fruit and vegetables export is realized on a choosy European Union (EU) market, the increase of export can be achieved only by honoring the strict standards and having adequate certificates. A chance for increase in production and competitiveness is in interconnecting into clusters which have proven to be the best way of increasing the market competitiveness and survival in an era of globalization and rule of multinational companies.